Research on the design of new high-strength and high-toughness steel and its manufacturing parameters. Issue 1 (1st December 2022) - Zuo, Duo; Liang, Liang; Wu, Teng; Li, Zhao; Xiong, Weiliang; Wu, Run
Abstract: The lightweight of the steel structure can be achieved by the high strength and high toughness of steel. In this paper, the composition design and optimal manufacturing process of the experimental steel were investigated. The fine and uniform microstructure of tempered sorbite can be obtained under the conditions of TMCP (Thermo Mechanical Control Process), 920 °C quenching, and 650 °C tempering for the steel by micro-alloying with Nb, V, and Ti. The steel has properties as follows: yield strength of 1015 MPa, tensile strength of 1076 MPa, elongation of 14.5%, and -40 °C AKV 81 J. The parameters of quenching and tempering heat treatment have a decisive influence on the size and distribution of ferrite grains and precipitates of tempered sorbite.